Immunologic evaluation and validation of methods using synthetic peptides derived from Mycobacterium tuberculosis for the diagnosis of tuberculosis infection (2013)
The goal of this study was to demonstrate the usefulness of an enzyme-linked immunosorbent assay (ELISA) for the serodiagnosis of pulmonary tuberculosis (PTB) and extrapulmonary TB (EPTB). This assay used 20 amino acid-long, non-overlapped synthetic peptides that spanned the complete Mycobacterium tuberculosis ESAT-6 and Ag85A sequences. The validation cohort consisted of 1,102 individuals who were grouped into the following five diagnostic groups: 455 patients with PTB, 60 patients with EPTB, 40 individuals with non-EPTB, 33 individuals with leprosy and 514 healthy controls. For the PTB group, two ESAT-6 peptides (12033 and 12034) had the highest sensitivity levels of 96.9% and 96.2%, respectively, and an Ag85A-peptide (29878) was the most specific (97.4%) in the PTB groups. For the EPTB group, two Ag85A peptides (11005 and 11006) were observed to have a sensitivity of 98.3% and an Ag85A-peptide (29878) was also the most specific (96.4%). When combinations of peptides were used, such as 12033 and 12034 or 11005 and 11006, 99.5% and 100% sensitivities in the PTB and EPTB groups were observed, respectively. In conclusion, for a cohort that consists entirely of individuals from Venezuela, a multi-antigen immunoassay using highly sensitive ESAT-6 and Ag85A peptides alone and in combination could be used to more rapidly diagnose PTB and EPTB infection.